2012
DOI: 10.1021/ic202436j
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide(III) Complexes with Ligands Derived from a Cyclen Framework Containing Pyridinecarboxylate Pendants. The Effect of Steric Hindrance on the Hydration Number

Abstract: Two new macrocyclic ligands, 6,6′-((1,4,7,10-tetraazacyclododecane-1,7-diyl)bis(methylene))dipicolinic acid (H2DODPA) and 6,6′-((4,10-dimethyl-1,4,7,10-tetraazacyclododecane-1,7-diyl)bis(methylene))dipicolinic acid (H2Me-DODPA), designed for complexation of lanthanide ions in aqueous solution, have been synthesized and studied. The X-ray crystal structure of [Yb(DODPA)](PF6)·H2O shows that the metal ion is directly bound to the eight donor atoms of the ligand, which results in a square-antiprismatic coordinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 74 publications
8
74
0
Order By: Relevance
“…The synthesis of the ligands L 1 – L 3 are depicted in Scheme and Scheme . 1,7‐Dipicolinic cylen precursor 1 was obtained according to literature procedures . Alkylation of 1 with methyl iodide afforded a mixture of the monomethylated ( 2 ) and dimethylated ( 3 ) cyclen precursors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of the ligands L 1 – L 3 are depicted in Scheme and Scheme . 1,7‐Dipicolinic cylen precursor 1 was obtained according to literature procedures . Alkylation of 1 with methyl iodide afforded a mixture of the monomethylated ( 2 ) and dimethylated ( 3 ) cyclen precursors.…”
Section: Resultsmentioning
confidence: 99%
“…In previous works,, it has been shown that the macrocyclic ligand H 2 L 1 (Scheme ) forms eight‐coordinate complexes with Ln ions both in the solid state and in solution. The presence of the methyl substituents in positions 1 and 7 of the cyclen moiety introduces a certain degree of steric hindrance on the picolinate pendants that prevents the coordination of water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…31 A similar effect has been observed in a related system published recently by Platas-Iglesias and co-workers. 21 Thus, the chemist studying chelates that undergo very rapid dissociative water exchange should understand that changes in the dissociative water exchange rate are intrinsically linked to the hydration state of the chelate, both through static structural effects described by Parker and co-workers 33 and through the dynamic effects described herein.…”
Section: Discussionmentioning
confidence: 95%
“…36-41 However, our chosen approach is unique in that in addition to a chelate with very fast dissociative water exchange kinetics the same methods can be applied to generate an isomeric chelate with slower dissociative water exchange kinetics. 34,42 This allows us, for the first time, to compare the effects of accelerating inner-sphere dissociative water exchange on relaxivity.…”
Section: Introductionmentioning
confidence: 99%